PENGARUH JUMLAH UANG BEREDAR, KURS US DOLLAR DAN INDEKS HARGA KONSUMEN TERHADAP INDEKS HARGA SAHAM SEKTOR PERDAGANGAN DI BURSA EFEK INDONESIA - Nurlia Rahmatika (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study aims to determine the analysis of the influence of the Money Supply (M2), the USD Exchange Rate and the Consumer Price Index. The research methodology used is a quantitative method with time series data and data sources derived from secondary data obtained from the Indonesia Stock Exchange. The sampling technique uses purposive sampling method with monthly data and research period from January 2009 to December 2016. The data analysis technique used is multiple linear regressions. The results of this study indicate that partially the independent variable Amount of Money has a positive and significant effect on the Trading Sector Stock Price Index. While the independent variable USD Exchange Rate and Consumer Price Index has a negative and significant effect on the Trading Sector Stock Price Index. Meanwhile, simultaneously the independent variable consisting of Money Supply, the USD Exchange Rate and the Consumer Price Index together have a significant relationship to the dependent variable, namely the Trade Sector Stock Price Index.